EVOLUTION OF JAPAN’S PACIFIST TO REALIST DIPLOMACY: FROM YOSHIDA SHIGERU TO FUMIO KISHIDA - Govindasamy, Geetha (WILAYAH: The International Journal of East Asian Studies, 2023)
The paper seeks to answer two questions. What are the newer security policies promoted by Japan and are they significant in empowering Tokyo to become an international security and foreign policy leader? In order to answer these questions, the paper examined the implementation of realism diplomacy through actions taken in the past as well as present. Findings suggests that for decades, the Yoshida Doctrine was the basis for Japan’s foreign policy when the state’s priority was economic prosperity and security. However, the severity of the current security environment surrounding Japan desperately needs a different set of foreign policies and diplomacy. The transformation started during Shinzo Abe’s administration which has now been continued by Fumio Kishida, albeit with slight changes here and there. Kishida’s values based realism policies are aimed at protecting Japan as well as transforming the state into a key global player and contributor in security issues. Strengthening defence capabilities, enhancing multilaterism and improving relations with neighbours have indeed transformed Japan into a more responsible, capable and respected global player. Having said that, Kishida does face numerous challenges internally in sustaining his policy priorities.